Knowledge and practice of healthy behaviors for dementia and stroke prevention in a United States cohort - Jasper R. Senff; Reinier W. P. Tack; Benjamin Y. Q. Tan; Savvina Prapiadou; Tamara N. Kimball; Sharon Ng; Jonathan Duskin; Mark Jun Shah-Ostrowski; Courtney Nunley; H. Bart Brouwers; Zeina Chemali; Gregory Fricchione; et al. (Scientific Reports)
Abstract At least 45% of dementia and 60% of stroke cases are due to modifiable risk factors and could in part be prevented through healthy behavior. This cross-sectional study clustered and characterized a U.S. cohort’s knowledge and practice of healthy behavior associated with dementia and stroke. A total of 1,478 participants (mean age: 45.5 years, 51.8% female) were included. A hierarchical cluster analysis was performed to identify clusters based on the level of knowledge and practice of healthy behavior. We defined knowledge as recognizing eight modifiable risk factors (alcohol, diet, smoking, physical activity, sleep, stress, social relationships, and purpose in life) as important. We defined practice as complying with validated recommendations for each healthy behavior. Three clusters emerged: (I) high knowledge and poor practice (II) high knowledge and good practice, and (III) lower knowledge and poor practice. Participants in the high knowledge and good practice cluster were statistically significantly older, more educated, perceived fewer barriers (financial and time limitations), and more facilitators (motivation or knowing someone with dementia or stroke) compared to the other clusters. Our findings could assist in tailoring preventative strategies to enhance knowledge, translating knowledge into practice, and addressing particular facilitators and barriers per identified cluster.